On the Time of Streets - Sérgio Barreiros Proença (In_Bo)
The editorial examines the relation between streets and time through five interrelated Fragments. Fragment#1 focuses on the etymology of rua, highlighting its dual role as place and itinerary. Fragment#2 describes streets as wrinkles of time, embodying continuity and change. Fragment#3 explores both cyclical and linear time perspectives. Fragment#4 looks at streets through the lens of urban morphology. Fragment#5 reflects on editorial choices for this issue, emphasizing diverse perceptions of time and space.